Psychometric Validation of the Spanish SET-M Using Bootstrap Exploratory Graph Analysis in Nursing Students From Argentina and Spain - Carolina Astoul Bonorino; Dolores Latugaye; Virginia La Rosa-Salas; Marta Lizarbe Chocarro; Eliana Escudero Zuñiga; Aaron Travezaño-Cabrera (My University, 2025)
INTRODUCTION: The Evaluation of Learning and Performance standard of the International Nursing Association for Clinical Simulation and Learning proposes evaluating all simulation-based experiences. Over the years, multiple instruments have been designed to evaluate simulation. The Simulation Effectiveness Tool-Modified (SET-M) was developed by Leighton and colleagues in English in 2015. This tool has been translated and validated in different languages and cultures, presenting stable psychometric properties. Although a Spanish validation of the instrument has been found, it was conducted with medical students after participating in telesimulation. To date, no validation has been found for its use after face-to-face simulation with Spanish-speaking nursing students. This study aims to validate the psychometric properties of the SET-M in advanced nursing bachelor's students engaged in face-to-face simulation from 2 Spanish-speaking countries. METHODS: A multicenter, cross-sectional, analytical, and psychometric validation study was conducted. The sample consisted of 232 students from the final 2 years of their Bachelor's Degree in Nursing at 2 privately managed universities, 1 in Argentina and the other 1 in Spain. The bootstrap Exploratory Graphical Analysis (EGA) approach was used to determine the structural consistency and stability of the items. RESULTS: An EGA identified 4 communities with adequate stability and structural consistency values. Furthermore, the SET-M was found to be invariant among nursing students in Argentina and Spain. CONCLUSIONS: The Spanish version of the SET-M demonstrated adequate psychometric properties, confirming its validity and reliability for assessing simulation-based education effectiveness in undergraduate nursing students in Argentina and Spain. This study provides a valuable tool for self-assessment in simulation education within Spanish-speaking contexts.
Keywords: Psychology; Reliability (semiconductor); Psychometrics; Exploratory analysis; Nursing; Nurse education; Applied psychology; Educational measurement; Validity; Medical education; Exploratory research; Psychometric testing; Item analysis; Item response theory; Construct validity; Clinical psychology; MEDLINE; Test validity; Measure (data warehouse); Exploratory factor analysis; Content validity; Nursing Minimum Data Set; Reliability (semiconductor); Psychometrics; Exploratory analysis; Nurse education; Educational measurement; Validity; Exploratory research; Psychometric testing; Simulation Training standards; Simulation Training standards; Simulation Training standards; Adult; Adult; Adult; Argentina; Argentina; Argentina; Cross-Sectional Studies; Cross-Sectional Studies; Cross-Sectional Studies; Education, Nursing, Baccalaureate; Education, Nursing, Baccalaureate; Education, Nursing, Baccalaureate; Educational Measurement methods; Educational Measurement methods; Educational Measurement methods; Female; Female; Female; Humans; Humans; Humans; Male; Male; Male; Psychometrics; Psychometrics; Psychometrics; Surveys and Questionnaires; Surveys and Questionnaires; Surveys and Questionnaires; Spain; Spain; Spain; Students, Nursing psychology; Students, Nursing psychology; Students, Nursing psychology; Reproducibility of Results; Reproducibility of Results; Reproducibility of Results; Young Adult; Young Adult; Young Adult; Health Sciences Medicine Physiology Simulation-Based Education in Healthcare; Health Sciences Nursing Research and Theory Nursing education and management; Health Sciences Health Professions General Health Professions Interprofessional Education and Collaboration